APPLYING BERTOPIC MODELLING ON UNITED NATIONS GENERAL DEBATES 1970-2016 DATASET TO IDENTIFY ECONOMIC DEVELOPMENT AND DEMOCRACY ISSUES - Anshori, Muhammad Fikry (Aliansi, 2025)
This article applies topic modeling to examine the discussion on economic development and democracy in United Nations General Debates over time and finds their spread across different countries. To achieve that aim, this article uses openly available debate transcripts from 1970 to 2016 to explore how distributed economic development and democracy are in the debates. Then, this article identifies the key themes of economy and democracy discussed throughout these debates using BERTopic as the topic modeling framework. By doing that, this article provides insights into the extent to which United Nations member states articulate economic progress with democracy based on common keywords and their patterns from the topic modeling. The main finding is that the intertwining between economic development and democracy issues emerges as the comprehensive development agenda became more prominent, such as the Millennium Development Goals (MDGs) in 2000 and their transition to Sustainable Development Goals (SDGs) in 2015. That contributes to knowing how economy and democracy emerge as a concern in the United Nations, the biggest platform for multilateral diplomacy.